Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Sambungan Air Minum Pada PDAM Tenggarong Seberang - Yonathan Palinggi; Novi Widya Asmara Ningrum (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract The purpose of this study was to analyze the effect of income variables, number of family members and the needs of influencing the demand for drinking water connections at the Tenggarong Seberang Branch Office of PDAM. This study used a research sample of 90 people with a probability sampling method. The analysis tool uses multiple regression analysis. The results showed that from the F test, it was found that F count 96.447> F table 2.47 so that it can be said that the variables of income, number of family members and needs together are able to show a significant effect on the demand for drinking water connections at the Tenggarong Seberang Branch Office of PDAM. Partially, the income variable, family member variable, need variable have a positive influence on the demand for drinking water connections. The variable of need has the most dominant influence on the demand for water connection, which is 0.617 or 61.7%, followed by the income variable of 0.588 or 58.8%, and the variable of the number of family members is 0.483 or 48.3%. Keywords : Customer Income, Number of Family Members, Needs, Connection Request